Clinical Outcome Assessments Toolbox for Radiopharmaceuticals - Kunos, Charles A.; Capala, Jacek; Dicker, Adam P.; Movsas, Benjamin; Ivy, Susan Percy; Minasian, Lori M. (Frontiers in Oncology, 2019)
For nearly 40 years, the U.S. National Cancer Institute (NCI) has sponsored health-related quality-of-life (HRQOL) and symptom management measures in oncology clinical trials and research as a method for including a cancer patient’s experience during and after treatment. The NCI’s planned scope for HRQOL, symptom and patient-reported outcomes management research is explained as it pertains to radiopharmaceutical clinical development. An effort already underway to support protocol authoring via an NCI Cancer Therapy Evaluation Program (CTEP) Centralized Protocol Writing Service (CPWS) is described as this service aids incorporation of HRQOL, symptom and patient-reported outcomes management research into sponsored protocols.